PROFIL GAYA BERPIKIR SISWA DALAM MEMECAHKAN MASALAH FISIKA MELALUI PEMBELAJARAN ONLINE BAGI SISWA DI SMAN 6 BORONG - Langut, Maria Ifenci; Kaleka, Melkyanus Bili Umbu; Doa, Hamsa (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
This study aims to describe students' thinking styles in solving physics problems through online learning for students of class XI MIA SMA Negeri 6 Borong. This type of research uses descriptive research. The subjects in this study were students of class XI SMA Negeri 6 Borong totaling 22 people. While the object in this study is the profile of students' thinking styles in solving physics problems through online learning. The data collection technique in this research is a questionnaire. The results obtained from this research show that students' thinking styles in solving physics problems are categorized as good, with the percentage gain of each indicator, namely for concrete sequential indicators with a percentage of 67.97% in good categories, abstract sequential indicators with a percentage of 61.65% in good categories, indicators Concrete random has a percentage of 57.95% with good category, and 55.80% abstract random indicator with sufficient category. The average percentage gain of the four indicators is 60.84%. This shows that the students' thinking style in solving physics problems at SMA Negeri 6 Borong is categorized as good.